TEACHING SPEAKING BY USING STORY COMPLETION TECHNIQUE - Syaprizal S.; Gita Priska (LP4MK STKIP PGRI Lubuklinggau, 2018)
These research conducted the answer question “was it significantly effective to teach speaking by using Story Completion Technique to the eighth grade students of SMP Muhammadiyah 1 Lubuklinggau.” The objective of this research was to find out whether or not it is significantly effective to teach speaking by using Story Completion Technique to the eighth grade students of SMP Muhammadiyah 1 Lubuklinggau. The total population on this research was 145 students coming from 5 classes. The sample was taken by cluster random sampling. The sample of this research was VIII.3 as the sample with the total number of sample was 30 students. Based on the matched t-test calculation.It was found out that tobtain is 6.66 and the value or score of ttable is 1.699. the tobtain is higher than ttable (6.66 ≥ 1.699). It was found out the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted . It means that it was significantly effective to teach speaking by using Story Completion Technique to the eighth grade students of SMP Muhammadiyah 1 Lubuklinggau in academic year of 2018/2019.